Impact of Adenoviral Stool Load on Adenoviremia in Pediatric Hematopoietic Stem Cell Transplant Recipients. Issue 6 (June 2015) - Srinivasan, Ashok; Klepper, Corie; Sunkara, Anusha; Kang, Guolian; Carr, Jeanne; Gu, Zhengming; Leung, Wing; Hayden, Randall T.
Abstract : Background: Adenoviremia adversely affects prognosis in the post-hematopoietic stem cell transplant setting. Methods: We sought to determine retrospectively the cutoff load of adenovirus in the stool as a predictor of adenoviremia, in children who underwent an allogeneic hematopoietic stem cell transplant. The prevalence of sapovirus, norovirus and astrovirus in the stool was also studied. Results: The study cohort consisted of 117 patients, of which 71 (60%) had diarrhea. Adenovirus was detected in the stool in 39 of 71 (55%) patients. Age ⩽10 years ( P = 0.05; odds ratio: 2.57; 95% confidence interval: 0.98–6.75) and male sex ( P = 0.04; odds ratio: 2.67; 95% confidence interval: 1.02–6.99) increased risk for detection of adenovirus in stool on univariate analysis. Coinfections with enteric pathogens were infrequent. Viral load >10 6 copies/g stool predicted adenoviremia with a sensitivity and specificity of 82%. Sapovirus, norovirus and astrovirus were detected in 3, 4 and 1 patient, respectively. Conclusions: Quantitative detection of adenovirus in stool may have implications for preemptive therapy. Testing for other enteric viruses may have implications for infection control.